2021
DOI: 10.3390/w13091290
|View full text |Cite
|
Sign up to set email alerts
|

Silver Doped Zinc Stannate (Ag-ZnSnO3) for the Photocatalytic Degradation of Caffeine under UV Irradiation

Abstract: Contaminants of emerging concerns (CECs) spread across a wide range of organic product compounds. As biorecalcitrants, their removal from conventional wastewater treatment systems remains a herculean task. To address this issue, heterogenous solar driven advanced oxidation process based-TiO2 and other semiconductor materials has been extensively studied for their abatement from wastewater sources. In this study, we have synthesized by hydrothermal assisted co-precipitation Ag doped ZnSnO3. Structural and morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Owing to their high potential applicability in wastewater treatment in a relatively cheap and green manner, the photocatalytic materials are now being intensively investigated [15][16][17]. Titanium dioxide (TiO 2 ) is the most used solid for photocatalytic reactions, due to its high photocatalytic efficiency, biological and chemical inertness, low toxicity and easy availability at an acceptable price [18].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their high potential applicability in wastewater treatment in a relatively cheap and green manner, the photocatalytic materials are now being intensively investigated [15][16][17]. Titanium dioxide (TiO 2 ) is the most used solid for photocatalytic reactions, due to its high photocatalytic efficiency, biological and chemical inertness, low toxicity and easy availability at an acceptable price [18].…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of ternary metal oxides with controllable sizes and shapes has been an active research field in the past two decades, because of their size-and shape-dependent physical, chemical, optical, electronic, and catalytic properties [1][2][3]. In particular, the two zinc stannates, Zn 2 SnO 4 and ZnSnO 3 , have caused considerable attention due to their wide applications in dye-sensitized solar cells (DSSCs) [4,5], gas sensors [6,7], lithium-ion batteries [8,9], and photocatalysts [10,11]. Zn 2 SnO 4 and ZnSnO 3 are both photovoltaic and photocatalytic materials with band gaps of about 3.6 eV and 3.2 eV, and the Femi energy level of ZnSnO 3 is higher than that of Zn 2 SnO 4 [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc stannate-based materials exhibited remarkable performance in the fields of solar cells, sensors, catalysis, and battery applications. Silver-doped zinc stannate was synthesized using a hydrothermally assisted coprecipitation route, which exhibited an efficient photocatalytic degradation performance of caffeine under UV irradiation . It was reported that bismuth stannate-based films, on a glass substrate, displayed remarkable self-cleaning capability against organic dyes under visible light …”
Section: Introductionmentioning
confidence: 99%
“…Silver-doped zinc stannate was synthesized using a hydrothermally assisted coprecipitation route, which exhibited an efficient photocatalytic degradation performance of caffeine under UV irradiation. 10 It was reported that bismuth stannate-based films, on a glass substrate, displayed remarkable self-cleaning capability against organic dyes under visible light. 11 A series of metal stannate systems, as electrocatalysts, have been reported for the electrochemical reduction of carbon dioxide.…”
Section: ■ Introductionmentioning
confidence: 99%